Desenvolvimento de um software para dimensionamento de fundações do tipo tubulão para torres de linhas de transmissão - Marinho, Renata de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Electricity is an indispensable resource for modern life. In this sense, the development of a region is strongly driven by the growth of the electric sector, in which Brazil, with its vast territorial extension and great capacity in energy resources, largely renewable, but away from the consumer centers, requires the construction of a extensive network of energy transmission. Since transmission lines are responsible for transmitting energy or signals at long distances and in view of their importance in the context of the country's electricity sector, it is essential to develop a good design of these constructions from its foundation to the elements that make up its structure, so that they resist the submitted efforts and play their role in a safe way. The design of tower foundations of electric power transmission lines is usually developed from the typical formulations for projects of the current constructions. The present work presents the development of a software to assist in the design of the foundations elements of freestanding towers of transmission lines according to the norms in force in the country and using the Python programming language. In order to validate the results obtained by the implemented software, an example of application with the results compared to that obtained from an analytical solution is presented. With the analysis of the results, it is concluded that the developed software provides the expected results, guaranteeing efficiency in the design of foundations of towers of electric power transmission lines.
Monografia
Keywords: Projeto de estruturas; Torres autoportantes; Linhas de transmissão; Python; ENGENHARIAS::ENGENHARIA CIVIL